A phase II clinical study of combining FOLFIRI and bevacizumab plus erlotinib in 2nd-line chemotherapy for patients with metastatic colorectal cancer. Issue 30 (July 2017) - Zhao, Zhifei; Li, Jianxiong; Ye, Rui; Wu, Xuan; Gao, Lingling; Niu, Baolong
Abstract : Abstract: We conducted an open-label single-arm phase II study by combining irinotecan (FOLFIRI) and bevacizumab (BV) plus erlotinib (ER) in 2nd-line chemotherapy for patients with metastatic colorectal cancer (mCRC). Eligible mCRC patients received 1st-line standard chemotherapy but still had progressive disease. They were given FOLFIRI plus BV at 2.5 mg/kg on day 1 per 2-week cycle, and daily 150 mg ER. The primary endpoint is progression-free survival (PFS). A total of 122 patients enrolled in the study. Among them, 55.7% were male patients and median age was 58.4 years (29–72 years). Median PFS was 7.1 months (95% CI 4.3–10.2). Median overall survival (OS) was 13.5 months (95% CI 9.7–16.4). No patients had complete responses, 24 patients had partial response (19.6%) and 59 had stable disease (48.4%). The most frequent adverse event (AE) was rash, with 66 patients (54.1%) had grade 3/4 rash. Other frequent grade 3/4 AEs were fatigue (n = 36, 29.5%), bleeding (n = 31, 25.4%), neutropenia (n = 23, 18.9%), and platelets (n = 14, 11.5%). Combining FOLFIRI and BV plus ER in 2nd-line chemotherapy is efficient to treat mCRC patients with acceptable safety.